Bioinformatics analysis of amino acid decarboxylases related to four major biogenic amines in pickles. (1st November 2022) - Lin, Ze; Wu, Zheng-yun; Zhang, Wen-xue
Highlights: Amino acid decarboxylase (ADD) sequences vary lesser among bacterial species than between bacteria and fungi. ADD sequences in Lactobacillus are not always of high similarity with those in other bacteria. Most ADDs are predicted as stable cytosolic endoenzymes. Molecular docking results suggest that the components of pepper, chili, and ginger may inhibit AADs by binding with their active sites. Abstract: Microbial amino acid decarboxylases (AADs) produce biogenic amines (BAs) in fermented food. However, a systematic comparison of the AADs' properties from different microorganisms in pickle fermentation remains unexplored. Here, we bioinformatically analyzed the amino acid sequences of AADs corresponding to four major BAs for common microorganisms in pickle fermentation. We showed that their sequences, besides tyrosine decarboxylase, differed among microorganisms. Overall, the AAD sequences varied lesser among bacterial species than between bacteria and fungi, with those in Lactobacillus sharing occasionally high similarity with other bacteria. Most AADs were predicted as stable cytosolic endoenzymes. Molecular docking showed that most commonly used spice components in pickle production, especially pepper, chili, and ginger, strongly bind to the AAD active sites, thus may inhibit the enzymes and reduce the BA accumulation. This study provides insights for deeply understanding the different microbial AAD properties in pickle fermentation and reducing BAs by appropriately using spices.